Industrial training report: Hospital Canselor Tuanku Muhriz (HCTM) / Muhammad Zahid Hanafi Mohamad Azian - Mohamad Azian, Muhammad Zahid Hanafi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The IMD310 Industrial Training course is a core requirement for students pursuing the CDIM110 Diploma in Information Management at UiTM. It offers valuable hands-on experience in the information management field, which is essential for professional development. I completed my 8-week internship at the Public Health Unit of Hospital Canselor Tuanku Muhriz (HCTM) and the Department of Public Health Medicine at the Faculty of Medicine, UKM. These institutions focus on advancing public health within communities. Throughout my training, I actively participated in various outreach programs, particularly volunteering for the Inisiatif Komuniti Malaysia Madani Sihat (IKMAS) initiative in Kampung Orang Asli Pos Tenau, Felda Besout, and Felda Sungai Behrang. My role included serving as an official photographer and videographer, which enhanced my skills in event management and multimedia production. Additionally, I gained valuable insights into data management, public health strategies, and professional communication. This training has equipped me with essential knowledge and practical skills, preparing me for future endeavors in the information management sector.